Modifikasi Mesin Potong Rumput Tipe Gendong Menjadi Mesin Potong Padi (Mower) Untuk Meningkatkan Produksi Hasil Tani Pada Kelompok Tani Makmur - Ruzita Sumiati; Desmarita Leni; Fardinal Fardinal; Adriansyah Adriansyah; Veny Selviyanty YH (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The community service team from the Padang State Polytechnic majoring in Mechanical Engineering has implemented a community service program which is participated by members of the affluent farmer group, namely the local community, which is located in Batu Gadang, Kec. Lubuk Kilangan which owns agricultural land. This community service provides rice mower machine assistance to affluent farmer groups. Community service is expected to be able to help all members of a prosperous farmer group, who previously needed a lot of manpower for post-harvest, now no longer need a lot of agricultural labor and also with this community service assistance, prosperous farmer groups can save time and costs for post-harvest. The high hopes of the community service team for affluent farmer groups are to be able to make the most of this machine and support the success of affluent farmer groups to increase rice production and overcome the need for extravagant labor at post-harvest time. And it is highly hoped that the prosperous farmer groups will be able to use this rice mower machine, and can assemble agricultural tools with a modification of the carrying type lawn mower to be used as a rice cutting machine.